2001
DOI: 10.1093/intimm/13.11.1405
|View full text |Cite
|
Sign up to set email alerts
|

Limited effect of chromatin remodeling on Dβ-to-Jβ recombination in CD4+CD8+ thymocyte: implications for a new aspect in the regulation of TCR β gene recombination

Abstract: We have generated mutant mice in which TCR beta chain enhancer (E(beta)) was replaced with the TCR alpha chain enhancer (E(alpha)). Using this mouse model, we analyzed (i) recombination status of the TCR beta chain genes after functional V(D)J rearrangements occurred in the first allele during double-negative (DN)-to-double-positive (DP) transition and (ii) involvement of E(beta) for the expression of rearranged TCR beta chain genes. Our data show that E(alpha) substituted for E(beta) function to express a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…However, positioned at their own chromosomal location, such reduced hubs mostly failed in sustaining recombination efficiently (41) (this study). More generally, even when promoting recombination within synthetic transgenes, TCR/Ig enhancers often do not work properly at heterologous sites (13,(41)(42)(43)(44). The discordant results are unlikely due to a loss of enhancer function at knockin alleles caused by gene targeting.…”
Section: Discussionmentioning
confidence: 99%
“…However, positioned at their own chromosomal location, such reduced hubs mostly failed in sustaining recombination efficiently (41) (this study). More generally, even when promoting recombination within synthetic transgenes, TCR/Ig enhancers often do not work properly at heterologous sites (13,(41)(42)(43)(44). The discordant results are unlikely due to a loss of enhancer function at knockin alleles caused by gene targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that the Eß-independent Jß accessibility could occur in a certain developmental stage where p53 expression is inactivated. Some studies have also shown that Eß-independent Jß accessibility increases during DN to DP thymocyte differentiation (20,31), and the DN to DP transition of thymocytes was suggested to be dependent on p53 inactivation (32). As p53 is known as a chromatin accessibility factor and p53-mediated chromosomal accessibility or inaccessibility is possible (33,34), it is possible that Jß loci become accessible to RAG-mediated cleavage in the absence of p53 during the progression of lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous iE promotes accessibility at a distance of at least 4 kb to assembled DJ H 1 complexes and, after V H -to-DJ H rearrangement, appears capable of stimulating transcription of an 5Ј germ-line V H promoter at a distance of 17.5 kb (45). Furthermore, iE can also replace E␤ function within the endogenous TCR␤ locus to promote D␤1 accessibility (39,40), a process dependent on activation of the D␤1 germ-line promoter (46,47), at a distance of 21 kb.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a 116-bp core fragment of human E␣ that lacks several trans-factor binding sites has been shown to promote the complete assembly of a transgenic TCR␦ minilocus (37). Furthermore, heterologous enhancer elements can promote accessibility in many contexts (38), including within the endogenous TCR␤ locus where E␣ and iE can replace E␤ function (39,40). To further evaluate the extent to which TCR␣͞␦ locus 3Ј enhancer identity may be critical for chromosomal V␣-to-J␣ rearrangement, we investigated whether E␣C or iE could substitute for E␣ function.…”
Section: E␦ Does Not Promote Efficient J␣ Accessibility When Located mentioning
confidence: 99%